2012
DOI: 10.1108/14777831211262936
|View full text |Cite
|
Sign up to set email alerts
|

CSR and sustainable development: are the concepts compatible?

Abstract: PurposeIn France, an application decree from February 2002 enumerates a series of operational indicators that companies must offer, including a number of accounting and financial items. The information expected notably includes working time organisation, gender equality, health and safety, disability policies, subcontractor arrangements, water, raw material and energy consumption and biodiversity efforts. The present study aims to account for the diversity of the social and environmental information that compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
0
11
0
3
Order By: Relevance
“…Recent studies have shown a possibility of tying corporate governance to CSR through shareholding structures and the presence of external directors on the board (Barnea and Rubin, 2010;Hollandts et al, 2011). This kind of disclosure enables stakeholders to gain a better understanding of executive governance and control and obtain information about how a firm is being managed and how it engages with society (Capron, 2011;Husser et al, 2012). Disclosing detailed information to all relevant parties appears to be more useful than isolated measures relating to governance mechanisms, such as a board size, composition, and/or executive compensation (Ben Barka and Hermalin and Weisbach, 2012).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Recent studies have shown a possibility of tying corporate governance to CSR through shareholding structures and the presence of external directors on the board (Barnea and Rubin, 2010;Hollandts et al, 2011). This kind of disclosure enables stakeholders to gain a better understanding of executive governance and control and obtain information about how a firm is being managed and how it engages with society (Capron, 2011;Husser et al, 2012). Disclosing detailed information to all relevant parties appears to be more useful than isolated measures relating to governance mechanisms, such as a board size, composition, and/or executive compensation (Ben Barka and Hermalin and Weisbach, 2012).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…A szakirodalmi keresés alapján az anyavállalati hatás, valamint a nemzetközi iránymutatások hatása is jelentős lehet (Husser et al, 2012). Ez a jelenség a CSR-kutatások alapján általánosságban hazánkban is kimutatható (Bank, 2017), de a mi eseteinkben is speciálisan kirajzolódott.…”
Section: öSszefoglalás -A Fogyatékossággal éLő Emberek Foglalkoztatásunclassified
“…Jocelyn Hosser studied the historical development of the concept of CSR during the past five decades [5]. It was concluded from her study that there are many deficiencies in listing the factors that affect the development of corporate social responsibility.…”
Section: історичний розвиток концепції корпоративної соціальної відпоmentioning
confidence: 99%